An introduction to plant structure and development plant anatomy for the twenty-first century. - Beck, Charles B. (Cambrifge University, 2005)
Unlike many other plant anatomy textbooks, the 18 chapters in this volume incorporate information from the latest research in cellular and molecular biology as related to plant development. Topics include the integrative significance of plasmodesmata and the concept of the symplast, the concept of multicellularity, the role of the cytoskeleton in development, signal transduction, and the genetic control of development. Brief sections on evolution and function are also included. The textbook has been designed for undergraduate and graduate students with a basic knowledge of plant science. --Provided by publisher.